Does a Structured Gardening Programme Improve Well-Being in Young-Onset Dementia? A Preliminary Study. (August 2013) - Hewitt, Peter; Watts, Claire; Hussey, Jacqueline; Power, Kath; Williams, Tim
Introduction: Young-onset dementia affects about 1 in 1500 people aged under 65 years in the United Kingdom (UK). It is associated with loss of employment, independence and an increase in psychological distress. This project set out to identify the benefits of a 2 hours per week structured activity programme of gardening for people with young-onset dementia. Method: A mixed methods (qualitative and quantitative) study of therapeutic gardening for people with young-onset dementia, measuring outcomes for both participants with young-onset dementia and their carers, was used. Twelve participants were recruited from a county-wide mental health service for older adults, based on onset of dementia being before the age of 65 years (range 43–65 years). Of these, two participants dropped out and one died during the project. Measures included the Mini Mental State Examination (MMSE), Bradford Well-Being Profile, Large Allen Cognitive Level Screen (LACLS) and Pool Activity Level (PAL). Findings: Over a 1-year period the carers of the people with young-onset dementia found that the project had given participants a renewed sense of purpose and increased well-being, despite cognitive functioning continuing to decline during this period. Conclusion: This study suggests that a meaningful guided activity programme can maintain or improve well-being in the presence of cognitive deterioration.